Aβ-Induced Repressor Element 1-Silencing Transcription Factor (REST) Gene Delivery Suppresses Activation of Microglia-Like BV-2 Cells. (22nd September 2020) - Yu, Tongya; Quan, Hui; Xu, Yuzhen; Dou, Yunxiao; Wang, Feihong; Lin, Yingying; Qi, Xue; Zhao, Yanxin; Liu, Xueyuan
Abstract : Compelling evidence from basic molecular biology has demonstrated the crucial role of microglia in the pathogenesis of Alzheimer's disease (AD). Microglia were believed to play a dual role in both promoting and inhibiting Alzheimer's disease progression. It is of great significance to regulate the function of microglia and make them develop in a favorable way. In the present study, we investigated the function of repressor element 1-silencing transcription factor (REST) in A β 1-42 -induced BV-2 cell dysfunction. We concluded that A β 1-42 could promote type I activation of BV-2 cells and induce cell proliferation, migration, and proinflammation cytokine TNF- α, IL-1 β, and IL-6 expression. Meanwhile, REST was upregulated, and nuclear translocalization took place due to A β 1-42 stimulation. When REST was knocked down by a specific short hairpin RNA (sh-RNA), BV-2 cell proliferation, migration, and proinflammation cytokine expression and secretion induced by A β 1-42 were increased, demonstrating that REST may act as a repressor of microglia-like BV-2 cell activation.